A new highly Zn2+-selective and "off–on" fluorescent chemosensor based on the pyrene group1. Issue 19 (7th October 2015) - Gao, Cunji; Zhu, Hongmei; Zhang, Mingliang; Tan, Ting; Chen, Jia; Qiu, Hongdeng
<x xml:space="preserve">Abstract</x> A highly zinc ion selective fluorescent chemosensor H2L based on a pyrene derivative was described. Importantly, this chemosensor can clearly distinguish Zn2+ from Cd2+.